Body mass index (BMI) of vegetarian and non-vegetarian children in Nepal - Acharya, Usha; Nakanishi, Jun (Journal of Health Promotion, 2021)
This article builds upon a study that aimed to evaluate the BMI differences among vegetarian and non-vegetarian children of Nepal and to recommend the diet practice of growing-age children. A descriptive cross-sectional study was conducted to determine physical growth and calculate the BMI values of 1251 Koiri and Yadav children aged 6-14 years who were selected for the study. Data were analyzed based on age, sex, vegetarian and non-vegetarian children. The average BMI value wt (kg)/ht (m2) of non-vegetarian children was significantly higher than the vegetarian in both sex groups. The finding of the study clearly shows that vegetarian diet practice in children is smaller than the non-vegetarian. The study recommends that vegetarian group children required more plant source protein food for favorable growth and balanced physical growth, good health status to maintain different physical and mental disabilities, and enhance school performances. Protein requirements on vegetarian children may be fulfilled if the diet includes different varieties of plant-based protein sources in their regular meals. Therefore, the study recommends that vegetarian families regularly include protein-rich foods for the growing-age children, such as legumes, beans, different seeds and nuts, and a variety of protein sources.